2015
DOI: 10.1128/jcm.03465-14
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization–Time of Flight and Comparative Genomic Analysis of M-18 Group A Streptococcus Strains Associated with an Acute Rheumatic Fever Outbreak in Northeast Italy in 2012 and 2013

Abstract: f Acute rheumatic fever (ARF) is a postsuppurative sequela caused by Streptococcus pyogenes infections affecting school-age children. We describe here the occurrence of an ARF outbreak that occurred in Bologna province, northeastern Italy, between November 2012 and May 2013. Molecular analysis revealed that ARF-related group A Streptococcus (GAS) strains belonged to the M-18 serotype, including subtypes emm18.29 and emm18.32. All M-18 GAS strains shared the same antigenic profile, including SpeA, SpeB, SpeC, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Other notable features of GAS epidemiology include the propensity for long-term fluctuations in disease rates, such as the recent substantial increase in scarlet fever in the United Kingdom in 2013/2014 ( 4 ), and the association with outbreaks. GAS outbreaks are strongly associated with long-term-care or institutional facilities ( 5 8 ) and occur less often within whole communities ( 9 11 ). The introduction of new emm genotypes ( 12 , 13 ) or the acquisition of prophages harboring virulence genes by previously circulating GAS are the primary mechanisms underpinning these outbreaks ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other notable features of GAS epidemiology include the propensity for long-term fluctuations in disease rates, such as the recent substantial increase in scarlet fever in the United Kingdom in 2013/2014 ( 4 ), and the association with outbreaks. GAS outbreaks are strongly associated with long-term-care or institutional facilities ( 5 8 ) and occur less often within whole communities ( 9 11 ). The introduction of new emm genotypes ( 12 , 13 ) or the acquisition of prophages harboring virulence genes by previously circulating GAS are the primary mechanisms underpinning these outbreaks ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…pharyngitis outbreaks and the subsequent onset of acute rheumatic fever [28][29][30]. A relatively high prevalence (9%) of emm18 among iGAS was reported one in Italian study, 2003-2005 [28].…”
Section: Discussionmentioning
confidence: 96%
“…Multilocus sequence typing and SNP-based analysis, though limited, confirmed the relatedness of the three isolates. Further analysis of the three genomes revealed that all three isolates possessed the hasABC operon encoding for the hyaluronic acid capsule and considered to be an important virulence factor of emm 18 strains [ 29 , 34 ]. As reported elsewhere for emm 18 isolates, the three outbreak isolates also harboured the speA gene encoding the SpeA superantigen [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAS M types have been highlighted as an important determinant to clarify the distribution and development of ARF outbreaks. Genetic variation in the emm gene, which encodes the M protein, has been correlated with varying ARF incidence, particularly the occurrence of GAS serotype M18 isolates (20)(21)(22). The association of several outbreaks of ARF with the circulation of mucoid GAS strains in the community has been reported (23).…”
Section: Discussionmentioning
confidence: 99%